2019
DOI: 10.1021/acs.inorgchem.9b00830
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Investigation of the S–N2System up to the Megabar Range: Synthesis and Characterization of the SN2Solid

Abstract: Sulfur and nitrogen represent one of the most studied inorganic binary systems at ambient pressure on account of their large wealth of metastable exotic ring-like compounds. Under high pressure conditions however, their behavior is unknown. Here, sulfur and nitrogen were compressed in a diamond anvil cell up to about 120 GPa and laser-heated at regular pressure intervals in an attempt to stabilize novel sulfur-nitrogen compounds. Above 64 GPa, an orthorhombic (space group Pnnm) SN2 compound was synthesized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 84 publications
(165 reference statements)
1
17
0
Order By: Relevance
“…These authors found that the reaction of elemental sulfur and N 2 gas in a diamond anvil cell at pressures above 60 GPa with laser heating produces an orthorhombic (P nnm ) SN 2 compound. 40 The lattice parameters of this material obtained from powder diffraction data match closely the theoretically pre-dicted crystalline structure of SN 2 . 37 Single crystal X-ray diffraction analysis revealed a CaCl 2 -type structure composed of edge-sharing SN 6 octahedra with N atoms that are triply coordinated by S atoms (Fig.…”
Section: Dalton Transactions Perspectivesupporting
confidence: 68%
See 2 more Smart Citations
“…These authors found that the reaction of elemental sulfur and N 2 gas in a diamond anvil cell at pressures above 60 GPa with laser heating produces an orthorhombic (P nnm ) SN 2 compound. 40 The lattice parameters of this material obtained from powder diffraction data match closely the theoretically pre-dicted crystalline structure of SN 2 . 37 Single crystal X-ray diffraction analysis revealed a CaCl 2 -type structure composed of edge-sharing SN 6 octahedra with N atoms that are triply coordinated by S atoms (Fig.…”
Section: Dalton Transactions Perspectivesupporting
confidence: 68%
“…8). 40 The SN 2 solid was found to be metastable down to ca. 20 GPa, at which point it dissociates into its elements.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The samples were mainly characterized by single-crystal (sc-XRDp) and powder x-ray diffraction (XRDp) measurements. The subscript "p" in sc-XRDp emphasizes the very small, just a few microns size of the single crystals, for which a special approach to the high-pressure XRD data acquisition and analysis was recently developed in high-pressure crystallography [28], and its reliability demonstrated numerous times [35][36][37]. The x-ray diffraction data were acquired at the P02.2 and 13-IDD beamlines of PETRA III and the APS, respectively.…”
Section: A Experimental Methodsmentioning
confidence: 99%
“…The analysis procedure includes the peak search, the removal of the diamond anvil's parasitic reflections and saturated pixels of the detector, finding reflections belonging to a unique single crystal, the unit-cell determination and the data integration. The crystal structures were then solved with the SHELXT (Sheldrick, 2008) analysis was previously demonstrated and successfully employed (Bykova, 2015;Laniel et al, 2019;Laniel, Winkler, Bykova et al, 2020;.…”
Section: Synthesis and X-ray Diffraction In The Laser-heated Diamond mentioning
confidence: 99%